tranScriações - Rancan, Ubirajara (Editora Oficina Universitária, 2022)
The images in this book could be safely called "domestic", both because they were originally made for personal consumption, so to speak, and because most of them appeared in interior spaces in which I lived, or where for some time I found myself. . The period covered by them ranges from 2006 to 2022, although most are from the last 4 years. If what was necessary for choosing the images shown here was the author's taste, the vehicle to guide him [and sometimes to disturb him] was his own humoral fluidity... To contemporize it, the always very judicious observations of Renata Souza, an early supporter to whom she will be indefinitely indebted. As if such personal support were not enough, Renata was responsible for the entire conception of the book that is available here. To Re, therefore, all my recognition, my entire sphere. To Giovanni Alves, father of the idea, my thanks To Lucia Dantas, Renata Souza, José Justo, Márcio Benchimol and Paulo Jesus - to whom I owe comments for the brilliance and scope of which I did not consider these images of mine worthy -, all mine. Giovanni Alves [father of the idea], Rodolfo Cruz, Mariângela Spotti Lopes Fujita, Arlenice Almeida da Silva, Colleagues at the Library and Editorial Laboratory of the Faculty of Philosophy and Sciences [especially Gláucio Rogério de Morais ], my most sincere thanks for the friendship, for the constant encouragement and support, for the competence and dedication. Ubirajara Racan